Terminal deoxynucleotidyltransferase: the story of an untemplated DNA polymerase capable of DNA bridging and templated synthesis across strands. (December 2018) - Loc'h, Jérôme; Delarue, Marc
Graphical abstract: Highlights: TdT has been known for more than 50 years as an untemplated DNA polymerase. However, it was recently shown to be able to bind to a DNA synapsis in solution. It was subsequently shown that TdT has in trans templated polymerase activity. New crystal structures show TdT caught in the act of DNA synthesis across strands. This dual activity of TdT can be understood in the context of its biological role. Abstract : Terminal deoxynucleotidyltransferase (TdT) is a member of the polX family which is involved in DNA repair. It has been known for years as an untemplated DNA polymerase used during V(D)J recombination to generate diversity at the CDR3 region of immunoglobulins and T-cell receptors. Recently, however, TdT was crystallized in the presence of a complete DNA synapsis made of two double-stranded DNA (dsDNA), each with a 3′ protruding end, and overlapping with only one micro-homology base-pair, thus giving structural insight for the first time into DNA synthesis across strands. It was subsequently shown that TdT indeed has an in trans template-dependent activity in the presence of an excess of the downstream DNA duplex. A possible biological role of this dual activity is discussed.